2002
DOI: 10.1002/acp.758
|View full text |Cite
|
Sign up to set email alerts
|

Signal‐detection models as tools for interpreting judgements of recollections

Abstract: This paper considers how the two-criterion signal-detection model can be used to interpret judgements of recollection from the remember-know paradigm. We propose that, among other uses, the model can be applied to discriminate results that provide strong evidence for the influence of multiple memory processes from results that are merely consistent with the assumption of such influences. The specific logic motivating this approach is that results falsifying the two-criterion signal-detection model provide stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Second, the results of the ROCs analyses strongly support the idea that the distinct states of consciousness gauged with R and K responses in our experiment represent two distinct sources or components of memory that do not result from variations in response criteria/decision processes along a single memory trace (e.g., see also Conway, Dewhurst, Pearson, & Sapute, 2001;Reder et al, 2000;Rotello et al, 2004 who have reached the same conclusions). While this conclusion only applies to our paradigm and does not rule out definitively one-dimensional SD models (see Hirshman et al, 2002), it reinforces the idea that perceptual priming modulates the creation of new episodic memories independently of familiarity or know judgments, especially when the nature of the recollected details (as the sound context in our study) becomes critical (Banks, 2000). Table 3 Cumulative proportions of hits and FAs and sensitivity measures (d 0 ) for each z-ROCs point (R and RK) according to the three priming conditions (''no-priming'', ''low-priming'' and ''high-priming'') Furthermore, the words that were associated with the creation of new episodic memories in the subsequent recognition task were subject to more perceptual priming during incidental encoding (RT differences between ''no-priming'', ''low-priming'' and ''high-priming'' conditions) than words that were subsequently judged to be known or forgotten, which did not yield any significant differences between priming conditions at encoding.…”
Section: Discussionmentioning
confidence: 80%
“…Second, the results of the ROCs analyses strongly support the idea that the distinct states of consciousness gauged with R and K responses in our experiment represent two distinct sources or components of memory that do not result from variations in response criteria/decision processes along a single memory trace (e.g., see also Conway, Dewhurst, Pearson, & Sapute, 2001;Reder et al, 2000;Rotello et al, 2004 who have reached the same conclusions). While this conclusion only applies to our paradigm and does not rule out definitively one-dimensional SD models (see Hirshman et al, 2002), it reinforces the idea that perceptual priming modulates the creation of new episodic memories independently of familiarity or know judgments, especially when the nature of the recollected details (as the sound context in our study) becomes critical (Banks, 2000). Table 3 Cumulative proportions of hits and FAs and sensitivity measures (d 0 ) for each z-ROCs point (R and RK) according to the three priming conditions (''no-priming'', ''low-priming'' and ''high-priming'') Furthermore, the words that were associated with the creation of new episodic memories in the subsequent recognition task were subject to more perceptual priming during incidental encoding (RT differences between ''no-priming'', ''low-priming'' and ''high-priming'' conditions) than words that were subsequently judged to be known or forgotten, which did not yield any significant differences between priming conditions at encoding.…”
Section: Discussionmentioning
confidence: 80%
“…However, it is useful to consider whether or not the data are also consistent with a single-process, signal detection account. In the case of remember/know (familiar) paradigms, the most widely cited model is the two-criteria signal detection model (Donaldson, 1996;Hirshman & Henzler, 1998;Hirshman, Lanning, Master, & Henzler, 2002;Inoue & Bellezza, 1998). Indeed a recent search of the Social Science Citation Index indicated that the Donaldson (1996) article had been cited 119 times.…”
Section: Discussionmentioning
confidence: 99%
“…These memory-strength/decision process accounts have now been shown not to provide an adequate general account of remembering and knowing (see, e.g., Conway et al, 2001;Gardiner, Ramponi, & RichardsonKlavehn, 2002), although more sophisticated dualcomponent accounts based on a similar kind of approach are proving more successful (e.g., Rotello, Macmillan, & Reeder, in press;Yonelinas, Dobbins, Szymanski, Dhaliwal, & King, 1996). Nonetheless, as Hirshman and his colleagues have suggested (Hirshman, Fisher, Henthorn, Arndt, & Passannante, 2002;Hirshman, Lanning, Master, & Henzler, 2002), there may still be some theoretical value in applying the single trace-strength model in some circumstances-for example, to obtain evidence for whether one can discount an explanation in terms of decision processes in those particular circumstances.…”
Section: University Of Sussex Brighton Englandmentioning
confidence: 99%
“…Individual t tests for voice congruency effects as measured by these A9 estimates (which we will also not report in detail) merely reflected those for the simple response proportions and did not materially alter the conclusions to be drawn. Thus, the results of the signal detection analyses serve mainly to allow us to discount the possibility that the changes in awareness with respect to voice congruency effects might be explained simply in terms of decision processes (Hirshman, Fisher, et al, 2002;Hirshman, Lanning, et al, 2002).…”
Section: Signal Detection Analysesmentioning
confidence: 99%